Visible-light-induced dearomative spirocyclization of N-benzylacrylamides toward perfluorinated azaspirocyclic cyclohexadienones. Issue 22 (31st May 2017) - Tang, Shi; Yuan, Li; Li, Zeng-Zeng; Peng, Zhi-Yuan; Deng, You-Lin; Wang, Liang-Neng; Huang, Gui-Xiu; Sheng, Rui-Long
Graphical abstract: Highlights: Novel synthetic route toward perfluorinated azaspirocyclic cyclohexadienones. Novel visible-light-induced dearomatizing spirocyclization N -benzylacrylamides using R f I or R f Br as fluorine sources. Mild reaction conditions and broad substrate scope. General incorporation of a variety of perfluorinated groups. Abstract: A feasible approach to 2-azaspirocyclic cyclohexadienones via visible-light-induced perfluoroalkylation cyclization of N -benzylacrylamides was reported. Using R f -X (X = I or Br) as the R f radical source, the reaction underwent a cascade radical addition/dearomative cyclization process by Ir photocatalyst, leading to various 2-azaspiro[4.5]deca-6, 9-diene-3, 8-diones bearing perfluorinated groups including CF3, n- C3 F7, n -C4 F9, n -C6 F13, n -C8 F17, n -C10 F21, CH2 CF2 and CF2 CO2 Et.